Endothelin receptor antagonists: a new therapeutic option for improving the outcome after solid organ transplantation? - Göttmann, Uwe; Woude, Fokko J. van der; Braun, Claude (Current vascular pharmacology, 2003)
Initially described as the most potent vasoconstrictor peptide, endothelin (ET) has also been shown to possess extraordinary immunomodulatory and proinflammatory properties. Because of this broad spectrum of biological activities, a possible role of the ET-system in solid organ transplantation has soon become a focus of research. Several studies demonstrated a pathogenetic involvement of ET in ischemia/reperfusion injury of heart, liver, kidney, and lung grafts. ET accumulates during cold storage of organs and can be detected in the effluent preservation solution. In addition ET is very, likely to play a pivotal role in the development of chronic rejection, which represents the major cause of late allograft loss. Increased expression of components of the ET-system has been described in areas of neointimal proliferation, a hallmark of chronic graft rejection. Both selective ET-A as well as non-selective ET-A/B receptor antagonists improved histomorphological and functional sequelae of chronic rejection. However these data have largely been derived from experimental animal transplantation, and ET receptor blockers have only recently been introduced in clinical medicine. A significant number of investigational drugs are now being tested in humans, with a main focus on cardiovascular diseases, such as congestive heart failure and pulmonary hypertension. First results have markedly dampened the initial enthusiastic vision of ET receptor blockers being organoprotective super-weapons. Thus the clinical potential of ET antagonists in general, and especially in solid-organ transplantation, is still to be defined.